2022
DOI: 10.3390/vaccines10081305
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal Immunization of SARS-CoV-2 Original Strain Trimeric Spike Protein Associated to CpG and AddaS03 Adjuvants, but Not MPL, Provide Strong Humoral and Cellular Response in Mice

Abstract: Despite the intramuscular route being the most used vaccination strategy against SARS-CoV-2, the intradermal route has been studied around the globe as a strong candidate for immunization against SARS-CoV-2. Adjuvants have shown to be essential vaccine components that are capable of driving robust immune responses and increasing the vaccination efficacy. In this work, our group aimed to develop a vaccination strategy for SARS-CoV-2 using a trimeric spike protein, by testing the best route with formulations con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Regarding survival and body weight lost, nonvaccinated animals succumbed to infection, while vaccination by both routes prevented viral spread into distal areas of the brain and protected all infected animals. These results are in line with other studies showing the effectiveness of different vaccine formulations administered by different routes [36] and indicate that our vaccine candidate is effective irrespective of the administration route. However, major differences between s.c. and i.n.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding survival and body weight lost, nonvaccinated animals succumbed to infection, while vaccination by both routes prevented viral spread into distal areas of the brain and protected all infected animals. These results are in line with other studies showing the effectiveness of different vaccine formulations administered by different routes [36] and indicate that our vaccine candidate is effective irrespective of the administration route. However, major differences between s.c. and i.n.…”
Section: Discussionsupporting
confidence: 93%
“…This could lead to heterogeneity in the response within mice groups, with a similar profile as it has been observed in previous studies using DNA vaccination ( 26 ). On the other hand, several published works have also shown that intradermal immunization can lead to strong immune activation following vaccination with different technologies in mice and humans and using low vaccine doses ( 59 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…A myriad of alternative adjuvants has been developed either with different chemical compositions (e.g. Freund's adjuvant, squalene, liposomes, MF59, lipids, cell exosomes or bacteria wall, etc), [18][19][20][21][22][23][24][25][26][27] or structurally different Al-based adjuvants, 15,28 but only a few have reached approval for human use as many exhibit either unacceptable side effects, insufficient immune responses, stability issues or difficulties in scaling-up. [29][30][31][32] Alternatively, the lack of cellular response in traditional Al-adjuvants can be compensated by the addition of immune orienteers (oligonucleotides, 33 imidazoquinoline, 34 TLR7 agonists 35 ).…”
Section: Introductionmentioning
confidence: 99%